Evidence of DDTs in the Greenland shark Somniosus microcephalus from Greenland seawaters - COTRONEI, SALVATORE; POZO, KARLA ANDREA; Audy, O.; Nielsen, J.; CORSOLINI, SIMONETTA (2016)
The Greenland Shark Somniosus microcephalus is a top predator of cold sea-waters that may reach a total length of up to six meters. For this reason, it is one of largest shark species in the world and presumably the largest fish in the Arctic . Very little is known about migrations or habitat preferences of this predator. Considering that the S. microcephalus is an opportunistic top predator, extremely long lived with slow growth, the bioaccumulation process of pollutants generated by human activities might be enhanced. The aim of this study was first to investigate the concentrations of DDTs and its metabolites in samples of liver and white muscle of S. microcephalus from Greenland seawaters, secondly to evaluate if the bioaccumulation is affected by sex.